2016
DOI: 10.1177/1350506816660992
|View full text |Cite
|
Sign up to set email alerts
|

‘Becoming more of myself’: Safe sensuality, salsa and ageing

Abstract: Ageing bodies are too often associated with invisibility or 'active' and 'successful ageing' discourses.Little research has explored the daily practices of ageing, gender and sexuality in midlife. Based on ethnographic research in salsa classes with women in their fifties, this paper explores the intersections and coproduction of ageing, femininity and heterosexualities within particular spaces. Single women in midlife initially felt unsure of the 'rules of the road', out of place in social space. Salsa class … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
(27 reference statements)
0
8
0
Order By: Relevance
“…They expressed difficulties, however, in finding spaces where they could socialise outside the home, where they could potentially meet new partners and also feel comfortable. As Sarah Milton (2017, 2018) has earlier argued, there are valuable insights from queer theory, about how sexuality and space co-produce each other, in that as one moves through space one is sexualised, or feels sexualised norms in particular ways, and in turn bodies sexualise the space (see, for example, Ahmed, 2006; Hubbard, 2000). Although this literature is focused on queer experiences of the heteronormativity of public space, the fundamental insight concerning the sexualisation of space resonates richly with Sarah’s study, as women spoke of feeling ‘out of place’ in social spaces in which sexual identities were regulated in particular ways.…”
Section: Research Settings and Methodsmentioning
confidence: 99%
“…They expressed difficulties, however, in finding spaces where they could socialise outside the home, where they could potentially meet new partners and also feel comfortable. As Sarah Milton (2017, 2018) has earlier argued, there are valuable insights from queer theory, about how sexuality and space co-produce each other, in that as one moves through space one is sexualised, or feels sexualised norms in particular ways, and in turn bodies sexualise the space (see, for example, Ahmed, 2006; Hubbard, 2000). Although this literature is focused on queer experiences of the heteronormativity of public space, the fundamental insight concerning the sexualisation of space resonates richly with Sarah’s study, as women spoke of feeling ‘out of place’ in social spaces in which sexual identities were regulated in particular ways.…”
Section: Research Settings and Methodsmentioning
confidence: 99%
“…Studies in other cultural contexts, likewise, suggest that gender scripts are not necessarily attenuated in older age. For instance, in her work with White British single women in mid-life attending salsa classes, Milton (2017) found that the classes allowed women to embody a 'sensual', 'independent', and 'socially active femininity' that challenges ageist assumptions. Yet they simultaneously produced the performance of a 'policed ' and 'age appropriate' femininity (p. 151, 155), and women's accounts also articulated concerns about respectability that were related to age.…”
Section: Discussionmentioning
confidence: 99%
“…The literature often interprets gendered variations as reflecting bodies’ marketability, but gendered experiences of managing embodiment online are also salient. Milton (2017) discusses the discomfort of midlife single women with various (offline) social spaces as contexts for finding partners, highlighting salsa classes’ appeal as a safe, age-appropriate context for managing embodiment; members of groups experiencing sizeism, ableism, and so on, may similarly adopt online dating as a less uncomfortable context for managing their embodied selves. Some physically disabled people view online dating as an effective vehicle for finding partners who accept their impairments (Saltes, 2013), although disclosing these online can also bring challenges, including rejection.…”
Section: Literature Reviewmentioning
confidence: 99%
“…With regard to physical characteristics, and in contrast to findings cited earlier, Table 2 provides strong evidence of a positive relationship between women’s BMI values and their odds of having met partners online; online meetings were particularly likely for the highest values, hinting at the relevance of niche dating sites, but the broader relationship is also consistent with generic sites and other online contexts being relatively effective meeting places for women with higher BMI values. Possible explanations include access to individuals attaching less importance to culturally idealised body shapes, less emphasis on physical characteristics within Internet-based relationship development, and, echoing Milton (2017), the discomfort relating to physical selves that some women experience in offline settings. While the result for women’s height is statistically non-significant ( p = 0.07), the substantially higher odds of online meetings for taller women could reflect active choices to seek partners online, arising from ‘thin markets’ with respect to tall(er) men, assuming heterosexual women still often prefer taller partners.…”
Section: Analysesmentioning
confidence: 99%